2017
DOI: 10.1111/ejn.13693
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐band oscillations during passive listening to metronome sounds reflect improved timing representation after short‐term musical training in healthy older adults

Abstract: Sub-second time intervals in musical rhythms provide predictive cues about future events to performers and listeners through an internalized representation of timing. While the acuity of automatic, sub-second timing as well as cognitively controlled, supra-second timing declines with ageing, musical experts are less affected. This study investigated the influence of piano training on temporal processing abilities in older adults using behavioural and neuronal correlates. We hypothesized that neuroplastic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 108 publications
2
22
0
Order By: Relevance
“…In another study, Fujioka et al (2009) showed that a beta decrease, which usually occurs after a regular musical beat, was absent after the omission of an expected beat. Furthermore, previous research (Fujioka and Ross, 2017) also showed that, after 1 month of musical training, beta activity increases during passive listening to a metronome for older adults. Moreover, based on topographical analysis, Mikutta et al (2014) suggested that musicians, compared to amateurs, have enhanced beta activity (between 19 and 23 Hz) in central cortical areas in response to emotional music.…”
Section: Inter-trial Phase Coherencementioning
confidence: 73%
See 2 more Smart Citations
“…In another study, Fujioka et al (2009) showed that a beta decrease, which usually occurs after a regular musical beat, was absent after the omission of an expected beat. Furthermore, previous research (Fujioka and Ross, 2017) also showed that, after 1 month of musical training, beta activity increases during passive listening to a metronome for older adults. Moreover, based on topographical analysis, Mikutta et al (2014) suggested that musicians, compared to amateurs, have enhanced beta activity (between 19 and 23 Hz) in central cortical areas in response to emotional music.…”
Section: Inter-trial Phase Coherencementioning
confidence: 73%
“…Findings in the current study highlight that more needs to be understood about the role of beta oscillation and visual perception. Together, these studies suggest that lower beta activity in AV perception compared to the auditory music perception for musicians might be associated with the potential involvement of beta oscillation in auditory-motor tasks, even with no intention for movement (Fujioka et al, 2009;Fujioka and Ross, 2017). This would suggest that for musicians, AV perception is modulated by activating auditory and sensory-motor, possibly also visual, networks over years of instrumental training (Trainor et al, 2009).…”
Section: Musicians and Sensory-motor Systemsmentioning
confidence: 92%
See 1 more Smart Citation
“…Careful measurement of the administration of treatment components is required for hypothesis testing of the mechanisms through which music treatment drives change in language skills (i.e., more broadly via the client–therapist relationship or changes driven by elements of music training that directly increase neural plasticity via shared brain networks for music language). Fujioka and Ross identified why treatment administration can be so difficult to capture in music interventions: there is an advantage to an ecologically valid method of engaging with music (like improvisational music therapy or Suzuki violin lessons) over a rigid laboratory‐based treatment in which dosage might be easier to capture. However, there are still available methods to quantify the administration of the components of a more naturalistic treatment, such that the dosage of key ingredients (hypothesized to be drivers of change) can be measured for each individual receiving treatment.…”
Section: Reporting Fidelity Of Music Treatmentmentioning
confidence: 99%
“…Any kind of emotion will be subject to the interaction of their feelings with subjective cognition. Influenced by the external world, individuals generate emotions interpreted by specific expressions and feelings, languages and behaviors (Fujioka & Ross, 2017;Trost, Frühholz, Schon et al, 2014). The music art beat exerts a great influence on the individual's behaviors such as attention, cognition, movement and memory.…”
Section: Introductionmentioning
confidence: 99%